2018
DOI: 10.1002/ejp.1242
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of the heart rate variability‐derived Analgesia Nociception Index in children anaesthetized with sevoflurane: An observational pilot study

Abstract: BackgroundThe heart rate variability (HRV)‐derived Analgesia Nociception Index (ANI™) is a continuous noninvasive tool to assess the nociception/antinociception balance in unconscious patients. It has been shown to be superior to haemodynamic variables in detecting insufficient antinociception in children, while little is known about its predictive value.MethodsThe primary objective of this prospective observational pilot study in paediatric surgical patients under sevoflurane anaesthesia was to compare the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 9 publications
3
8
0
Order By: Relevance
“…Recent studies performed in anesthetized children suggest that the heart rate variability analysis derived Analgesia Nociception Index (ANI™; Mdoloris Medical Systems, Loos, France) may provide a more sensitive assessment of the nociception/antinociception balance than hemodynamic parameters . These pediatric studies are in accordance with the results of studies investigating the performance of the ANI in anesthetized adult patients …”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Recent studies performed in anesthetized children suggest that the heart rate variability analysis derived Analgesia Nociception Index (ANI™; Mdoloris Medical Systems, Loos, France) may provide a more sensitive assessment of the nociception/antinociception balance than hemodynamic parameters . These pediatric studies are in accordance with the results of studies investigating the performance of the ANI in anesthetized adult patients …”
Section: Introductionsupporting
confidence: 65%
“…This and other findings can easily be compared to the results of our recent pediatric study with the ANI monitor, using exactly the same study design in patients aged between 2 and 12 years. ANI values <50 before opioid drug administration showed a significantly higher increase in approximately 10 units within 120 seconds, travelling across the 50 units border …”
Section: Discussionmentioning
confidence: 91%
“…31 A second study evaluating the score in the setting of paediatric anaesthesia found that ANI correlated better with a perceived (attending anaesthetist) lack of analgesia and the reestablishment of sufficient analgesia than HR. 32 In an investigation of the predictive value of ANI monitoring at the end of surgery, Boselli and colleagues 33 found that an ANI >50 had a high (92% for ANI >50) NPV for moderate-tosevere postoperative pain. However, to date, this study remains the only associated publication, and prospective validation of these results is required.…”
Section: Single-parameter Scoresmentioning
confidence: 99%
“…They found the Analgesia Nociception Index (ANI) more sensitive than pulse rate and mean blood pressure in detecting surgical noxious stimuli [34]. Also, Weber et al suggested monitoring devices using other parameters, such as skin conductance, plethysmography, pupillometry and heart rate variability were more sensitive assessment of the nociception/ antinociception balance than haemodynamic parameters [35].…”
Section: Case Nomentioning
confidence: 99%